The Dichotomy of Jus Ad Bellum and Jus Ad Bello in the 21st Century: Its Relevance and Reconstruction - Sefriani Sefriani (Faculty of Law, Universitas Padjadjaran, 2022)
Classical international law recognizes a rigid, autonomous, and independent dichotomy between jus ad bellum and jus in bello, which can result in the possibility of a just war being carried out illegally or vice versa. The dichotomy is considered a paradox. This study aims to analyze the relevance of the jus ad bellum and jus in bello dichotomy in the 21st century and to offer a more precise reconstruction of the relationship between the two. The results show that the rigid dichotomy between jus ad bellum and jus in bello is no longer relevant since the boundaries between war and peace are increasingly blurred. Nowadays, the world has experienced more widespread asymmetric warfare, as well as the use of modern super weapons. The dichotomy is also considered very eurocentrism and creates a paradox in international law. On the other hand, both have disproportionate use of force against the law and are not justified by military necessity. The reconstruction of the relationship between jus ad bellum and jus in bello must be dynamic, holistic, and harmonious. There should not be a rigid dichotomy, nor a rigid integration, which always places jus ad bellum above jus in bello or vice versa. Reconstruction of the relationship between the two must be based on the principle that a just war must be carried out in a just manner.DOI: https://doi.org/10.22304/pjih.v9n2.a4